Pretreatment verification of high dose rate brachytherapy plans using the 'magic phantom' system. (30th July 2015) - Espinoza, A; Petasecca, M; Cutajar, D; Fuduli, I; Howie, A; Bucci, J; Corde, S; Jackson, M; Zaider, M; Lerch, M L F; Rosenfeld, A B
Abstract: High dose rate (HDR) brachytherapy treatments can be incorrectly administered to patients due to human error and equipment malfunction. While the incidence rates of these events are low, an additional redundancy check could include independent verification of the plan prior to treatment. This work describes the verification of six patient HDR treatment plans using the 'magic phantom' (MPh) silicon diode array, and a specialized HDR position-time gamma analysis criteria. The possibility of accelerated treatment plan verification is additionally investigated by reducing the prescription dose to shorten the total time needed for measurement. The MPh system was able to determine the measured dwell positions and times from the six patient plans to within 1.3 mm and 0.3 s, respectively. Using the position-time gamma analysis, the delivery of all measured patient plans were found to pass this metric with pass rates of 100%. The approach of decreasing prescription dose gave equal pass rates to the full dose plan when evaluated using the criteria. It was identified that the total time for treatment verification is dependent on the number of needles used, and that a substantial decrease in the total time for verification could be made by reducing the prescription dose for plans containing a low number of needles. The application of this method may have the ability to streamline pretreatment verification of the afterloader delivery within the clinical setting.